Sudden Cardiac Arrest in a Patient With Apical Hypertrophic Cardiomyopathy: Case Report and a Brief Review of Literature. (January 2016) - Gupta, Tanush; Paul, Neha; Palaniswamy, Chandrasekar; Balasubramaniyam, Nivas; Aronow, Wilbert S.; Kolte, Dhaval; Khera, Sahil; Shah, Amar B.; Gass, Alan
Abstract : Apical hypertrophic cardiomyopathy (HCM) is a phenotypic variant of nonobstructive HCM, in which hypertrophy of the myocardium predominantly involves the left ventricular apex. It is common in Japanese and other Asian populations but is rare in the United States. Apical HCM has a relatively benign prognosis in terms of cardiovascular mortality; however, morbid events such as ventricular aneurysms, apical thrombi, diastolic dysfunction, atrial fibrillation, and myocardial infarction are not uncommon. We report a case of an 18-year-old white man who presented to our hospital after an out-of-hospital cardiac arrest. The patient had a witnessed collapse while playing basketball in the field. He was found to be pulseless and unresponsive by his coach, and cardiopulmonary resuscitation was immediately started. Upon arrival of emergency medical services, an automated external defibrillator advised shock and he was defibrillated thrice. Return of spontaneous circulation was achieved in 15 minutes. He was intubated for airway protection and was brought to the hospital. Therapeutic hypothermia was initiated. He demonstrated good neurological status after active rewarming. Subsequent cardiac magnetic resonance imaging was suggestive of apical HCM with right ventricular involvement. The patient underwent an implantable cardioverter defibrillator placement for secondary prevention and was subsequently discharged. In conclusion, apical HCM can rarely be associated with adverse cardiovascular events. The diagnosis may be missed on transthoracic 2-dimensional cardiac echocardiogram, and cardiac magnetic resonance imaging should be considered to exclude apical HCM in young patients who present after sudden cardiac arrest.